English for oral presentations : "And I… I speak the truth and nothing but the truth" / Marni Jamil - Jamil, Marni (Academy of Language Studies, 2024)
On the 6th of July 2023, an online webinar, “And I... I Speak the Truth and Nothing but the Truth” explored pivotal facets of ethics, credibility, accountability, and integrity in public speaking. This outstanding collaboration between two esteemed local higher learning institutions, namely Universiti Teknologi MARA Pulau Pinang Branch (UiTMCPP) and Universiti Sains Malaysia (USM), was led by Ms. Marni Jamil, a lecturer from the Academy of Language Studies, UiTMCPP. This project aligned with the goal of the Centre for Innovative Delivery and Learning Development (CIDL) UiTM to enhance student learning experience through formal collaborative teaching efforts. The primary objective of this webinar was to equip participants from the PHM2453A group, who were enrolled in the English for Oral Presentations (ELC590) course during the March - July 2023 semester, with knowledge and skills essential for success in both personal and professional aspects. Dr. Jamilah, the invited speaker, is a senior lecturer in the Speech Pathology Programme at the School of Health Sciences, USM. She also presides over the USM Health Campus Bilingual Toastmasters Club in District 102, Kelantan. Her wealth of expertise spans Applied Linguistics, Language and Culture, Intercultural Communication, and Intercultural Sensitivity. The webinar meticulously explored the significance of upholding elevated ethical standards. It highlighted integrating truthfulness into verbal expression and conduct, embracing accountability in communication, and establishing credibility among public speakers to build trust with the audience. Additionally, these principles are essential for individuals seeking to nurture constructive change through effective communication. The session also underscored the necessity of employing precise and impactful language, alongside strategic rhetorical devices in speech as emphasised throughout the ELC590 course.